Vliv smykové viskozity a elasticity na senzorickou viskozitu modelových kapalných potravin - P. Novotna; M. Houska; V. Sopr; H. Valentova; P. Stern (Czech Journal of Food Sciences, 1999)
The shear flow rheological properties of sugar solutions (70% w/w concentration) modified by different cellulose derivatives have been measured. Thickeners were expected to cause the viscoelastic behaviour of the resulting sol ution. Therefore, the elastic rheological parameters were measured by oscillatory shear technique (phase angle, elastic modulus) and also the first normal stress difference N1. The increase of thickener concen tration caused a moderate increase of non-Newtonian behaviour in the shear flow. The sensory viscosity (ra nged between 0 and 100%) was evaluated by five different methods - as an effort for stirring with teaspoon, time for flowing down the spoon, slurping from spoon, compression between tongue and palate and swallowing. The influence of shear viscosity and first normal difference on sensory viscosity was tested. Correlation procedu re between change of sensory viscosity .tlSE and change of shear viscosity .tlJ.Iz showed that only for swallowing there is a statistically evident dependence. The correlation between change of sensory viscosity t.SE and first normal stress difference N1 is not statistically evident. For all the methods of sensory evaluation the dependence between these parameters is only weak and indirect (with increasing normal stress difference the sensory viscosity is decreasing).